'Proud of what I do but often … I would be happier to say I drive trucks': Ambiguity in social workers' self-perception. (May 2019) - Beddoe, Liz; Staniforth, Barbara L; Fouché, Christa B
A public perception of social work research programme commenced 10 years after the introduction of limited professional registration of social workers in New Zealand. A first study explored public perceptions of social workers via a telephone survey. In a second study, social workers were asked, amongst other questions, how they thought the public would respond to the same questions about their profession that were asked in the first survey. An online survey accessed the views of 403 social workers and generated rich quantitative and qualitative responses, including to two very specific open questions (the focus of this article), first about social workers' expression of pride and second, felt stigma as potentially encountered in their professional and personal domains. These two concepts, pride and stigma, constitute organising constructs in this article, along with aspects of professional identity expressed in participants' imagining of the public view: ambivalence, hard work, difficult journeys, professional virtues, and being misunderstood. The complexity of a social work professional identity is further examined.